2021
DOI: 10.46918/point.v3i1.834
|View full text |Cite
|
Sign up to set email alerts
|

Long term Covid-19 terhadap Pasar Saham di Indonesia

Abstract: ABSTRAK Penelitian ini bertujuan meneliti pengaruh dari perkembangan penyebaran covid-19 di Indonesia terhadap pasar saham di Indonesia. Metode penelitian menggunakan data kasus baru dan kematian baru akibat covid-19, dan data penutupan dan Volume perdagangan IHSG yang kami kumpulkan dari periode tanggal 2 Maret sampai – 7 Januari 2021. Data tersebut kemudian kami uji menggunakan structure equation modeling (SEM) Partial Least Square (PLS) dengan bantuan aplikasi WarpPLS 7.0. Dalam penelitian ini kami te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Thus, the COVID-19 pandemic in Malaysia could have a positive and significant impact. These results are in accordance with the research conducted by Hidayat, Maulana, and Arief (2021), which found that in the long term, COVID-19 had a positive and significant impact on the JCI performance.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the COVID-19 pandemic in Malaysia could have a positive and significant impact. These results are in accordance with the research conducted by Hidayat, Maulana, and Arief (2021), which found that in the long term, COVID-19 had a positive and significant impact on the JCI performance.…”
Section: Discussionsupporting
confidence: 92%